Cattle Development in Kerala Trends and Prospects - K N Nair (Economic and Political Weekly September 1-8, 1990, 1990)
In there pars between 1964-65 and 1978- 79 Kerala witnessed a rapid increase in milk production which has been attributed to increased productivity of milch animals brought about through genetic improvements. This evaluation of the organised development of animal husbandry in the state, which commenced during the First Five-Year Plan, reviews the factors facilitating the spread of crosspreeding. The paper examines trends such as the extent of utilisation of artificial insemination services, changes in the composition of cattle population, contribu-tion of breed improvement to productivity of milch animals, demand for and returns from milk production and concludes with comments on the prospects for cattle development and milk production